Deaf Culture, Cochlear Implants, and Elective Disability - Tucker, Bonnie Poitras (The Hastings Center report, 1998)
The use of cochlear implants, especially for prelingually deafened children, has aroused heated debate. Members and proponents of Deaf culture vigorously oppose implants both as a seriously invasive treatment of dubious efficacy and as a threat to Deaf culture. Some find these arguments persuasive; others do not. And in this context arise questions about the extent to which individuals with disabilities may decline treatments to ameliorate disabling conditions. When they do so, to what extent may they call upon society to provide supportive services and accommodations?